A dictionary of abbreviations used in reptile descriptions - Darko, Yaa Adarkwa; Voss, Olaf; Uetz, Peter (Zootaxa, 2022)
Species are usually described by morphological terms. In order to simplify and shorten descriptions these are often abbreviated (e.g., SVL for snout-vent-length). However, there has been no systematic attempt to define and standardize such terms or their abbreviations. Here we present an initial list of 594 unique abbreviations from a total list of 1,223 abbreviations collected from >50 reptile species descriptions, resulting in a non-redundant list of 344 abbreviations. Most of these abbreviations describe either meristic characters such as scale counts (46%) or measurements such as SVL (snout-vent-length) (30%). The remainder describe presence/absence states, colors, or formulas such as ratios. We highlight the common problem of synonyms and homonyms, i.e., different terms and abbreviations for the same character or the same term for different characters. We propose to standardize definitions of terms and abbreviations in future species descriptions. In order to future-proof species descriptions for machine-readability such as text-mining, standardization is needed for all species descriptions in biology, not just reptiles.